Pemodelan laju pelepasan dan waktu tempuh radionuklida dalam air tanah pada calon lokasi penyimpanan lestari limbah radioaktif tingkat tinggi di P. Genting, Karimunjawa - Perpustakaan UGM, i-lib ([Yogyakarta] : Pusat Studi Lingkungan Hidup,UGM, 1998)
ABSTRACT In the event of supporting the long term national energy need, in the near future Indonesia will build several nuclear power plants (NPPs). Feasibility study held by consultant appointed by Indonesian government, highly indicated that the first NPP will be built in Muria, Jepara (NEWJEC, 1996). It is a general rule that for every countries operating NPPs, they always face the problem of management of high-level radioactive waste generated by those NPPs. Computer simulation has been conducted to the transportation of radionuclides released from the Near-Field of the proposed high-level radioactive waste repository facility, in the basalt formation at Genting Island, Karimunjawa. The simulation of performance assessment of the proposed ultimate repository, has integrated all the data relevant to the construction of NPP program as well as to the proposed high-level radioactive waste repository facility in. Indonesia. The simulation was conducted by using computer program, PAGAN, designed by Sandia National Laboratories, New Mexico. Of the 11 long-lived radionuclides having various retardation factors, C-14, Tc-99, and 1-129 showed the dominant release rates, whose values are 100Cila, 61,6 Ci/a, and 7,67 Ci/a consecutively. Nuclides C-14 and 1-129 have reached the boundary of exclusion zone, six years after the loss of institutional control. The concentrations of the 11 nuclides when reaching the exclusion zone boundary varied in the order of 10.23 to 10.29 alms.